Dynamic growth risk of incidentally detected gallbladder polyps–A retrospective, single-center analysis - Sophia Heinrich; Piet Janko ten Thoren; Patrick Behrendt; Jakob Hagenah; Heiner Wedemeyer; Andrej Potthoff; Benjamin Maasoumy (PLoS ONE, 2025)
Background Size of gallbladder polyps (GP) is considered as a relevant risk factor for neoplastic polyps. However, the definitive impact is an ongoing debate. Current German and European guidelines recommend surveillance for GP > 6 mm and cholecystectomy for GP > 10 mm over a period of two to five years. We aimed to analyze the dynamic growth of gallbladder polyps. Methods Patients at Hanover Medical School who underwent sonography from 2001 to 2020 were retrospectively evaluated for growth rate (GR) of detected GP independent of the underlying primary disease. Only patients with at least one follow-up as well as accurate GP size data were included in the study. Results A number of 253 patients with GP were eligible. Median follow-up was 66 months (24–209 months). Median GR was −0.3 mm/year (IQR 0.79). A subgroup analysis (polyp size 6–10 mm) showed a positive GR in 20.3% of the cases with a median GR of 0.09 mm/year (IQR 0.17). Of note, in 46% of the patients GP were not detectable at follow-up exam. Overall, two patients reached the indication for cholecystectomy (0.8%), whereas only a single patient developed histologically confirmed gallbladder cancer (0.4%). Logistic regression analysis did not reveal any risk factors associated with GP growth. Conclusion The majority of GP, which should be monitored within the current follow-up strategy, are no longer detectable sonographically over time or show a decreasing growth behavior. Only a minority shows a very slow positive GR and only a minority of patients develop malignancy.